10.61533 IMPLEMENTASI GREEN ACCOUNTING DAN INVESTASI LINGKUNGAN TERHADAP KINERJA KEUANGAN (STUDI KASUS DI PT INDOCEMENT TUNGGAL PRAKARSA TBK) - Rina Iryani (Jurnal Ilmiah Niaga Bisnis Elektronik, 2025)
This article aims to analyze the implementation of Green Accounting and Environmental Investment on the financial performance of the company at PT Indocement Tunggal Prakarsa Tbk, one of the largest cement companies in Indonesia that actively applies sustainability principles. The Methodology uses a quantitative approach with multiple linear regression analysis, and the data used are secondary data obtained from the company’s financial and sustainability reports for the period 2020 to 2023. The results show that Green Accounting and Environmental Investment both partially and simultaneously have a positive and significant effect on financial performance as measured by Return on Assets (ROA). These findings support Legitimacy Theory, which states that companies aligning their activities with societal values and expectations tend to gain social legitimacy and investor trust, ultimately leading to increased profitability. Therefore, the strategy of implementing green accounting and sustainable investment is proven to be effective in enhancing a company's financial performance.